Benign eyelid lesions and its histopathological picture: A case-series - Shalini Kumari (Journal of Family Medicine and Primary Care)
Our prospective case series evaluates the clinical feature, histopathological picture, and treatment of benign eyelid lesions in a tertiary referral setting. Participants were first nine patients referred to the author with unilateral eyelid swelling. Main outcome measures were clinical features, histopathological picture, and response to surgical intervention. Benign eyelid lesions in our case series were epidermal inclusion cyst, giant conjunctival inclusion cyst, epidermoid cyst, dermoid cyst, intradermal nevus, dermal nevus, apocrine hidrocystoma, capillary hemangioma, and lobular capillary hemangioma. The histopathological diagnosis of eight lesions were consistent with their respective clinical diagnosis, while one lesion was misdiagnosed. Surgical excision was done in all cases. One case underwent revision surgery for complication. This series highlights the importance of achieving higher diagnostic accuracy with thorough knowledge of clinical features and subsequent confirmation with histopathological analysis.